Efficiency of antifungal sublingual allergen-specific immunotherapy in patients under and over 50 years old with mild persistent and moderate bronchial asthma - Petrenko, Liudmyla; Rekalova, Elena (ScienceRise: Medical Science, 2017)
In Ukraine, the relative contraindication for allergen-specific immunotherapy (ASIT) in patients with bronchial asthma (BA) is age 50 years and older, which is substantiated by its efficiency reduce with age. The use of antifungal sublingual ASIT and its efficiency in older patients remain poorly investigated. Aim – research of antifungal sublingual allergen-specific immunotherapy (with mixed-allergens of household mold) in patients with mild and moderate bronchial asthma depending on the age (up to 50 years and older). Methods. A prospective, open, controlled, parallel, single-center study with clinical-functional and allergological examination in 45 patients with asthma in the remission stage with positive skin tests to fungal mixed-allergens was carried out. The patients were divided into 2 groups depending on the age: 27 patients from 20 to 50 years inclusive (mean age 39.6 ± 1.1 years) were included in the 1st group (the control group); 18 patients from 51 to 71 years old (mean age 57.1 ± 1.4 years) comprised the 2nd group (primary). The treatment was performed using sublingual method with fungal mixed-allergens (household mold mixture) (Aspergillus fumigatus, Aspergillus niger, Penicillium sp., Mucor sp., Rhizopus sp.) during the year. Results. The patients with mild persistent and moderate asthma over 50 years old initially differed from the younger patients by slightly worse functional respiratory rates (FEV1), and a lower percentage of patients with mild and uncontrolled asthma. The sublingual ASIT was effective regardless of age, including the patients over 50 years old. The results were confirmed by a positive dynamics of respiratory function indicators, decrease in skin sensitivity to fungal mixed-allergens, asthma transformation into controlled form in 83-89% of the patients. In the patients older than 50 years, the respiratory function dynamics was less pronounced. None of the patients had severe adverse effects. Mild adverse reactions occurred regardless of age in 96-98% of the patients with asthma, most often in the form of cough, runny nose, sneezing, sore throat, and skin itching. Conclusion. The sublingual ASIT with antifungal mixed-allergens in the interior premises in adult patients with mild persistent and moderate bronchial asthma is effective regardless of age, including the patients aged over 50, which was confirmed by improved respiration function, decreased skin sensitivity to fungal allergens, and improved life quality after 12 months therapy. Mild adverse effects happened regardless of age in 96-98% of the patients with asthma